Strategic Determinants of MSME Sustainability: Market Competition Mediation and Institutional Regulation Moderation Effects - Ariefah Sundari; Meithiana Indrasari; Sukesi Sukesi (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study examines the strategic determinants of MSME sustainability in East Java by investigating the effects of credit facilities, digital marketing, innovation strategy, pricing strategy, distribution strategy, circular economy, and inclusive partnerships. Market competition is positioned as a mediating variable, while institutional regulation acts as a moderating variable. A quantitative explanatory research design was employed using survey data collected from 396 MSMEs selected through simple random sampling across East Java. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that credit facilities, digital marketing, innovation strategy, pricing strategy, distribution strategy, circular economy practices, and inclusive partnerships significantly influence MSME sustainability. Market competition mediates the relationship between strategic factors and sustainability, indicating that competitive dynamics enhance the effectiveness of internal business strategies. Institutional regulation also moderates the relationship between market competition and sustainability by supporting a fair and conducive business environment. These findings demonstrate that MSME sustainability is determined by the interaction of strategic capabilities, competitive market conditions, and supportive institutional frameworks.